Plasma transfusion practices: A multicentre electronic audit. Issue 10 (14th September 2022) - Khandelwal, Aditi; Minuk, Leigh; Liu, Yang; Arnold, Donald M.; Heddle, Nancy M.; Barty, Rebecca; Hsia, Cyrus; Solh, Ziad; Shehata, Nadine; Thompson, Troy; Tinmouth, Alan; Perelman, Iris; et al.
Abstract: Background and Objectives: Plasma is often transfused to patients with bleeding or requiring invasive procedures and with abnormal tests of coagulation. Chart audits find half of plasma transfusions unnecessary, resulting in avoidable complications and costs. This multicentre electronic audit was conducted to determine the proportion of plasma transfused without an indication and/or at a sub‐therapeutic dose. Methods: Data were extracted on adult inpatients in 2017 at five academic sites from the hospital electronic chart, laboratory information systems and the Canadian Institute for Health Information Discharge Abstract Database. Electronic criteria for plasma transfusion outside recommended indications were: (1) international normalized ratio (INR) < 1.5 with no to moderate bleeding; (2) INR ≥ 1.5, with no to mild bleeding and no planned procedures; and (3) no INR before or after plasma infusion. Sub‐therapeutic dose was defined as ≤2 units transfused. Results: In 1 year, 2590 patients received 6088 plasma transfusions encompassing 11, 490 units of plasma occurred at the five sites. 77.7% of events were either outside indications or under‐dosed. Of these, 34.8% of plasma orders had no indication identified, and 62% of these occurred in non‐bleeding patients and no planned procedure with an isolated elevated INR. 70.7% of transfusions were under‐dosed. Most plasma transfusions occurred in the intensive care unit or the operating room. Inter‐hospital variability in peri‐transfusion testing and dosing was observed. Conclusion: The majority of plasma transfusions are sub‐optimal. Local hospital culture may be an important driver. Electronic audits, with definitions employed in this study, may be a practical alternative to costly chart audits.